Oblicz wartość wyrażenia:

(2x-3y)(2x+3y)-(x-3y)²-x(5x-y)-7xy

dla:
x = √2
y= 1/√3

mi wyszło tak:

4x² + 6xy - 6xy - 9y² + x² - 6xy +9y² -5x² + xy -7xy
po redukcji wyrazów podobnych

4x²+ x² - 6xy -5x² + xy - 7xy

po podstawieniu

8 + 2 - 6√2/√3 - 10 + √2/√3 - 7√2/√3 =
-5√2/√3 - -7√2/√3 = -12√2/√3 * √3/√3 = -12√6/3 = -4√6

1

Odpowiedzi

2010-03-03T19:48:31+01:00
(2x - 3y)(2x + 3y) - (x - 3y)² - x(5x - y) - 7xy = 4x² + 6xy - 6xy - 9y² - (x² - 2 • x •3y + x²) - 5x² + xy - 7xy = 4x² + 6xy - 6xy - 9y² - x² + 6xy - x² - 5x² + xy - 7xy = -3x² + 7xy - 7xy - 9y² = -3x² - 9y²

x = √2
y = 1/√3

-3 • (√2)² - 9 • (1/√3)² = -3 • 2 - 9 • 1/3 = -6 - 3